Facile One‐Pot Assembly of Push–Pull Imines by a Selective C–F Substitution Process in Aryl Fluorides. Issue 48 (9th November 2020) - Anga, Srinivas; Chandra, Shubhadeep; Sarkar, Pallavi; Das, Shubhajit; Mandal, Debdeep; Kundu, Abhinanda; Rawat, Hemant; Schulzke, Carola; Sarkar, Biprajit; Pati, Swapan K.; Chandrasekhar, Vadapalli; Jana, Anukul
Abstract : Herein, we report the synthesis of a series of push–pull imines by considering cyclic diamino substituent at the C‐centre and fluoroaryl substituent at the N‐centre. This has been achieved by a selective aromatic nucleophilic substitution of different fluoroarenes by N ‐H‐substituted N ‐heterocyclic imines (NHIs) at ambient conditions without any additional reagent. Solid‐state molecular structure analysis reveals the elongation of the central C–N bond of the imine functionality, which is consistent with the push–pull nature of these imines. The push–pull nature of these imines is further validated by computational studies. Abstract : A series of push–pull imines is reported, which are formed through a selective aromatic nucleophilic substitution of fluoroarenes by N–H substituted N ‐heterocyclic imines (NHIs), without the need of any additional catalyst. As a result, a straightforward methodology was developed for the formation of different fluoroaryl‐substituted push–pull imines.